The Relationship of Sirtuin 1 and Sirtuin 2 Expression with Clinicopathological Parameters in Non Small-Cell Lung Carcinomas - Fatma Cakmak Kazanci; Nagehan Barisik Ozdemir; Sibel Sensu; Cem Cahit Barisik (Haseki Tıp Bülteni)
Aim: Recent studies have shown that sirtuin signaling pathway activation could be a potential therapeutic target for future therapies and biomarkers for predicting prognosis in cancer. We aimed to investigate the association between Sirtuin 1 (SIRT1) and Sirtuin 2 (SIRT2) immunohistochemical (IHC) protein expression in tumors and clinicopathological parameters and survival profiles in non-small cell lung cancer (NSCLC) patients. Methods: This retrospective observational study reviewed lung resections (lobectomy, segmentectomy, wedge resection, and pneumonectomy) of 186 patients diagnosed with NSCLC (adenocarcinoma, squamous cell carcinoma, and adenosquamous carcinoma). SIRT1 and SIRT2 expression was classified as high and low expression based on the extent and intensity of IHC staining. Results: When there was advanced disease, a large tumor, and metastasis to lymph nodes, low levels of SIRT1 and SIRT2 expression were found. A positive correlation exists between high SIRT2 expression and longer overall survival. If SIRT1 and SIRT2 were both overexpressed (+/+), longer survival times were observed than in the group in which either of them was low (+/-, -/+, -/-) (p=0.01). Conclusion: Our research suggests that SIRT1 and SIRT2 may suppress tumor growth in NSCLC and serve as positive prognostic indicators.